Rancang Bangun Pengaruh Variasi Penambahan Tembaga Pada Paduan Aluminium Terhadap Konduktivitas Termal Bahan - Arya Wijaya Putra, I Gusti Ngurah; Astika, I Made; Sukadana, I Gusti Ketut (Teknik Desain Mekanika; Vol 10 No 3 (2021): Juli 2021 : Teknik Desain Mekanika, 2021)
Abstract The use of aluminum alloys in the industrial market encourages the development of new materials to obtain materials with better properties than conventional materials. Thish study aims to determine the effect ofhvariations in the addition of copper by 10%, 20%, 30% in aluminumhalloys on thermalhconductivity.hThe analysis in this studyhused independent variables, namely variationshin the additionhof copper by 10%, 20%, 30% in aluminumhalloys. Meanwhile, thehdependent variable is thermalhconductivity. The thermalhconductivity testhuses the TQhHeathTransfer Experiment BasehUnit tester. The dimensions of the testhspecimens were 30 mm inhdiameterhand 20hmm thick. The results of this study are the value of thermalhconductivity of materials in copper aluminum alloys have better thermal conductivity values along with the additionhof copper to aluminum alloys. Keyword: Aluminium alloy, copper, thermal conductivity